2020
DOI: 10.34024/rnc.2020.v28.10444
|View full text |Cite
|
Sign up to set email alerts
|

Immediate effect of foot reflexology in patients with diabetic neuropathy -Randomized Clinical Trial

Abstract: Introduction. Diabetic neuropathy (DN) is one of the most frequent chronic complications of type 2 diabetes mellitus (DM2). One technique capable of influencing the central and peripheral nervous system is foot reflexology (FR). Therefore, the objective of this study was to analyze the immediate effect of FR in DN type 2 patients. Method. This was a randomized controlled clinical trial, with 12 participants selected from a list of diabetic patients from the Basic Health Units of the city of Alfenas-MG. The sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
(12 reference statements)
0
0
0
1
Order By: Relevance
“…Rashwan et al, one of the studies investigating the effectiveness of reflexology, found that the ABI reached normal values in the reflexology applied group [42]. In the study of Megda et al, it was determined that the balance levels of diabetic patients improved after reflexology and a response occurred in muscle electrical activity [43]. In the study conducted by Silva et al in 2015, it was observed that it had a positive effect on elasticity/turgor, skin texture and integrity/skin peeling, and foot disorders in the application group [39].…”
Section: Discussionmentioning
confidence: 99%
“…Rashwan et al, one of the studies investigating the effectiveness of reflexology, found that the ABI reached normal values in the reflexology applied group [42]. In the study of Megda et al, it was determined that the balance levels of diabetic patients improved after reflexology and a response occurred in muscle electrical activity [43]. In the study conducted by Silva et al in 2015, it was observed that it had a positive effect on elasticity/turgor, skin texture and integrity/skin peeling, and foot disorders in the application group [39].…”
Section: Discussionmentioning
confidence: 99%
“…A reflexologia é uma técnica que aplica uma pressão suave nos pés ou nas mãos para provocar um estado de relaxamento e ajudar no processo de cura do próprio corpo (EMBONG et al, 2015). A reflexologia funciona de maneira semelhante à acupressão e à acupuntura, pois existem certos pontos nos pés e nas mãos que correspondem aos órgãos e glândulas do corpo (MEGDA et al, 2020).…”
Section: Considerações Sobre a Reflexologiaunclassified